Muon-spin relaxation and heat capacity measurements on the magnetoelectric and multiferroic pyroxenes LiFeSi2O6 and NaFeSi2O6 - Baker, P; Lewtas, H; Blundell, S; Lancaster, T; Franke, I; Hayes, W; Pratt, F; Bohaty, L; Becker, P (2010)
We present the results of muon-spin relaxation and heat capacity measurements on LiFeSi2O6 and NaFeSi2O 6. In synthetic samples of both compounds we see a single muon oscillation frequency consistent with commensurate magnetic structures below TN. In contrast, for a specimen of naturally occurring NaFeSi2O 6, in which multiferroicity has been observed, a rapid Gaussian depolarization of the muon polarization is observed instead, showing that the magnetic structure in this case is more complex. Heat capacity measurements reproduce the phase diagrams previously derived from other techniques and demonstrate that the main contribution to the magnetic entropy is associated with the buildup of correlations in the quasi-one-dimensional Fe3+ chains. © 2010 The American Physical Society.